The Value of Pre-Ablative I-131 Scan for Clinical Management in Patients With Differentiated Thyroid Carcinoma - van der Boom, Trynke; Zandee, Wouter T.; Dekkers, Claire C. J.; van der Horst-Schrivers, Anouk N. A.; Jansen, Liesbeth; Kruijff, Schelto; Brouwers, Adrienne H.; Links, Thera P. (Frontiers in Endocrinology, 2021)
Background: A diagnostic I-131 (Dx) scan is used to detect a thyroid remnant or metastases before treatment of differentiated thyroid cancer (DTC) with I-131. The aim of this study is to specify in which patients with DTC a Dx scan could have an additional value, by studying the effect of the Dx scan on clinical management. Methods Patients with DTC, treated with I-131 after thyroidectomy were included in this retrospective cohort study. Twenty-four hours after administration of 37 MBq I-131 a whole body Dx scan and an uptake measurement at the original thyroid bed were performed. Outcomes of the Dx scan and the subsequent changes in clinical management, defined as additional surgery or adjustment of I-131 activity, were reported. Risk factors for a change in clinical management were identified with a binary logistic regression. Results: In 11 (4.2%) patients clinical management was changed, including additional surgery (n=5), lowering I-131 activity (n=5) or both (n=1). Risk factors for a change in clinical management were previous neck surgery (OR 5.9, 95% CI: 1.4-24.5), surgery in a non-tertiary center (OR 13.4, 95% CI: 2.8 – 63.8), TSH <53.4 mU/L (OR 19.64, 95% CI: 4.94-78.13), thyroglobulin >=50.0 ng/L (OR 7.4, 95% CI: 1.6-34.9) and free T4 >=4.75 pmol/L (OR 156.8, 95% CI: 128.4-864.2) Conclusion: The Dx scan can potentially change clinical management before treatment with I-131, but the yield is low. A Dx-scan should only be considered for patients with a high pre-scan risk of a change in management, based on patient history and prior center-based surgical outcomes.